Cuidado de menores afectados por cáncer u otra enfermedad grave - Sánchez Trigueros, Carmen (Revista de Derecho, 2019)
The 21st disposal. two of the Law 39/2010 of 22 December, the General State Budgetfor 2011 (BOE of 23 December), introduced in Part II of the General Law of SocialSecurity a new Chapter IV regulates a novel e provide our Social Security system called“provision for the care of children affected by cancer or other serious disease. “ Thisnew provision would involve a legislative change, specifically the General Law of SocialSecurity (LGSS), the Statute of Workers and the Civil Service Basic Statute.
Keywords: Children; Shorter working hours; economic benefit; the conciliation between family and work